The resignification of borders as “genuinely ethical moment” - Valencia Rincón, Fernanda (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2022)
The work raises the need to give a new meaning to the borders as a genuinely ethical moment, while in this it would be possible to meet and recognize the “Other” from the tolerance of otherness and not as exclusion and marginalization of it, and the consequent discrimination and attack that this way of confronting the dignity of human beings entails.